Inulin as microencapsulating agent improves physicochemical properties of spray-dried aspalathin-rich green rooibos (Aspalathus linearis) extract with α-glucosidase inhibitory activity. (September 2018) - Miller, Neil; De Beer, Dalene; Aucamp, Marique; Malherbe, Christiaan J.; Joubert, Elizabeth
Graphical abstract: Highlights: Spray-drying had little effect on aspalathin content of green rooibos extract. Inulin lowered a w and improved wettability of spray-dried extract powder. Inulin improved clarity of extract, reconstituted to beverage concentration. Inulin did not affect α-glucosidase inhibitory activity of extract. Abstract: Limiting aspalathin degradation during spray-drying of green rooibos extract (GRE) is crucial to produce a functional food ingredient with antidiabetic properties. Retention of aspalathin in a GRE-inulin mixture (1:1, m/m) was not affected by process conditions (inlet air temperature, feed concentration and feed flow rate) tested according to a central composite design. Powder yield could subsequently be optimised by applying response surface methodology and desirability profiling. Inulin delivered a microencapsulated GRE powder with similar physicochemical properties to maltodextrin, commonly used by industry. An advantage of inulin, apart from its low glycaemic load and consequent suitability as functional ingredient, was that it improved wettability of GRE. Inulin had no effect on the intestinal α-glucosidase inhibitory effect of GRE. Aspalathin contributed to the enzyme inhibitory effect of GRE. Approximately 200 µg/mL GRE was required to have the same α-glucosidase inhibitory effect as 42 µg/mL acarbose.